Direct Observation of Conversion From Walled Cells to Wall-Deficient L-Form and Vice Versa in Escherichia coli Indicates the Essentiality of the Outer Membrane for Proliferation of L-Form Cells - Chikada, Taiki; Kanai, Tomomi; Hayashi, Masafumi; Kasai, Taishi; Oshima, Taku; Shiomi, Daisuke (Frontiers in Microbiology, 2021)
Gram-negative bacteria such as Escherichia coli are surrounded by an outer membrane, which encloses a peptidoglycan layer. Even if thinner than in many Gram-positive bacteria, the peptidoglycan in E. coli allows cells to withstand turgor pressure in hypotonic medium. In hypertonic medium, E. coli treated with a cell wall synthesis inhibitor such as penicillin G form wall-deficient cells. These so-called L-form cells grow well under anaerobic conditions (i.e., in the absence of oxidative stress), becoming deformed and dividing as L-form. Upon removal of the inhibitor, they return to the walled rod-shaped state. Recently, the outer membrane was reported to provide rigidity to Gram-negative bacteria and to strengthen wall-deficient cells. However, it remains unclear why L-form cells need the outer membrane for growth. Using a microfluidic system, we found that, upon treatment with the outer membrane-disrupting drugs polymyxin B and polymyxin B nonapeptide or with the outer membrane synthesis inhibitor CHIR-090, the cells lysed during cell deformation and division, indicating that the outer membrane was important even in hypertonic medium. L-form cells could return to rod-shaped when trapped in a narrow space, but not in a wide space, likely due to insufficient physical force. Outer membrane rigidity could be compromised by lack of outer membrane proteins; Lpp, OmpA, or Pal. Deletion of lpp caused cells to lyse during cell deformation and cell division. In contrast, ompA and pal mutants could be deformed and return to small oval cells even when less physical force was exerted. These results strongly suggest that wall-deficient E. coli cells require a rigid outer membrane to survive, but not too rigid to prevent them from changing cell shape.